Long-Term Follow-up Results of Primary Canaliculitis Patients - Emine Gökçen Bayuk; Emine Malkoç Şen; Fatma Çorak Eroğlu; Kübra Serbest Ceylanoğlu; Ebru Evren (Türk Oftalmoloji Dergisi, 2023)

(untitled)
Objectives:To evaluate the demographic characteristics, clinical presentation, microbiologic profile, and treatment results of patients with primary canaliculitis.Materials and Methods:Patients diagnosed and treated for primary canaliculitis between May 2014 and May 2021 were analyzed retrospectively.Results:There were 26 patients with primary canaliculitis, including 17 females (65.4%) and 9 males (34.6%) with a mean age of 50.6±16.4 years (range: 9-80 years). Canaliculitis affected the right eye in 11 patients, the left eye in 13 patients, and bilateral involvement was seen in 2 patients. Inferior canaliculus involvement was more frequent (73%). The most common complaint was epiphora (46.1%). Five patients (19.2%) were wrongly diagnosed as chronic conjunctivitis. The time interval between the beginning of symptoms and canaliculitis diagnosis was 18.2±14.3 months (range: 1-60 months). Canaliculotomy and curettage of canalicular content with dacryolith removal were performed in 23 patients. After surgery, antibiotic irrigation of the canaliculus was added to the treatment regimen in 12 of these 23 patients. Intracanalicular antibiotic therapy was administered to the remaining 3 patients. The most cultured organism was Actinomyces (6 patients). Gemella (1 patient), Porphyromonas (1 patient), Candida parapsilosis (1 patient), Citrobacter koseri (1 patient) were also grown in culture. The follow-up time of patients was 26.2±23.7 months (range: 6-83 months). All symptoms and findings resolved in all patients in one month. In two patients, recurrence occurred at 4 and 16 months after surgical treatment. With appropriate treatment, no further recurrence was seen in either patient over 24-month follow-up. One patient presented with iatrogenic canaliculus blockage during follow-up.Conclusion:Primary canaliculitis is often overlooked and can be misdiagnosed. The most common symptom was epiphora. All patients with epiphora and chronic conjunctivitis should be examined carefully for canaliculitis.